Also - Goodale, E. B. (Boston : Houghton Mifflin Harcourt, 2022)
This moving story follows one family through generations of time spent together and shows readers that memories allow us to connect to the past, the present, and also to each other.
Keywords: Families -- Juvenile fiction; Memory -- Juvenile fiction; Blueberries -- Juvenile fiction